2019
DOI: 10.1016/j.iref.2019.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric jump beta estimation with implications for portfolio risk management

Abstract: We evaluate the impact of extreme market shifts on equity portfolios and study the difference in negative and positive reactions to market jumps with implications for portfolio risk management. Employing high-frequency data for the constituents of the S&P500 index over the period 2 January 2003 to 30 December 2017, we investigate to what extent the portfolio exposure to the downside and upside jumps can be mitigated. We contrast the risk exposure of individual stocks with those of the portfolios as the number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…Eraker et al (2003) and Bollerslev et al (2016) provide further evidence of signicant risk premia for the jump component (Bollerslev et al, 2016;Eraker et al, 2003). Bollerslev et al (2016), Alexeev et al (2017) and Alexeev et al (2019) report that individual stocks respond dierently to the market jumps than the continuous counterparts suggesting dierent systematic risk dynamics attributed to the market jumps. Gajurel et al (2020) further show that systemic risk and systematic jump risk are related.…”
Section: Introductionmentioning
confidence: 79%
“…Eraker et al (2003) and Bollerslev et al (2016) provide further evidence of signicant risk premia for the jump component (Bollerslev et al, 2016;Eraker et al, 2003). Bollerslev et al (2016), Alexeev et al (2017) and Alexeev et al (2019) report that individual stocks respond dierently to the market jumps than the continuous counterparts suggesting dierent systematic risk dynamics attributed to the market jumps. Gajurel et al (2020) further show that systemic risk and systematic jump risk are related.…”
Section: Introductionmentioning
confidence: 79%
“…This could lead to an increase in portfolio variance and ultimately reduce the benefits of diversification for investors. Moreover, ignoring the asymmetry of returns could lead to under-diversification of the portfolio and consequently increase the vulnerability to unexpected extreme negative market changes (Alexeev et al 2019). Hedging against these extreme events could be difficult for investors unless their portfolios are large enough to bear such risk.…”
Section: Discussionmentioning
confidence: 99%
“…They also emphasize that, when comparing periods with larger and smaller portfolio recommendations, market volatility and correlations are lower in periods where large portfolios are recommended. Moreover, Alexeev et al (2019) showed that there is a difference in recommended portfolio size during more extreme bounces, with the number of portfolio holdings during extreme market downturns being twice as high as the number of holdings during positive market shifts. As they point out, the asymmetry was found to be more pronounced during events that occur during periods of high market volatility.…”
Section: Impact Of Crises On Risk Diversificationmentioning
confidence: 99%
“…Users can determine financial plans based on personal data [79]. This trend started from the discussions of insurance companies [78,85,86], who developed an integrated, knowledge-based model for AI (artificial intelligence), the robo-advisor [76,[81][82][83][84], to evaluate equity portfolios and study negative and positive reactions to portfolio risk management [77]. In addition, research on the adoption of mutual fund services has also been discussed [75].…”
Section: Research On Risk Management and Investmentmentioning
confidence: 99%
“…Regulators must secure and respect the conditions of the Portfolio risk management 34. The risk exposure of individual stocks with portfolios[77]…”
mentioning
confidence: 99%